Health promotion and pedagogical practice in physical education in the context of a public gym - John Koumantareas; Rogério Cruz de Oliveira (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2023)
The objective of the study was to understand the cultural dynamics related to health promotion in the context of the pedagogical practice of Physical Education professionals working in a public gym in a municipality of Baixada Santista, State of São Paulo – Brazil. In the method, an ethnography was proposed, which used participant observation over a semester, as well as conducting semi-structured interviews with two Physical Education professionals and five local residents and gym users, in addition to daily notes in the field notebook. Data analysis was done through triangulation and the use of non-aprioristic categories. Thus, the use of such strategies allowed us to immerse ourselves in the field of research and revealed the customs, practices, values and diversity of work inherent to the concepts, meanings and meanings attributed to that pedagogical practice. Finally, what can be stated is that in the daily rites of that cultural dynamic, the treatment given to the promotion of health is understood in a non-directive format about the steps that make up the pedagogical practice in Physical Education.